The inn - Patterson, James, 1947-; Fox, Candice (Little, Brown and Company, 2019)
The seclusion of the Inn at Gloucester suits former Boston police detective, Bill Robinson. Robinson runs the Inn and doesn't ask any questions, until Mitchell Cline arrives bringing drugs and violence to the peaceful inn.